2007
DOI: 10.1074/jbc.m700377200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Interleukin-7 Receptor α Promoter by the Ets Transcription Factors PU.1 and GA-binding Protein in Developing B Cells

Abstract: Signaling through the IL-7 receptor (IL-7R) is required for development and maintenance of the immune system. The receptor for IL-7 is heterodimeric, consisting of a common ␥ chain (␥c, encoded by Il2rg) and an ␣ subunit (IL-7R␣, encoded by Il7r). The Il7r gene is expressed specifically in the immune system in a developmental stage-specific manner. It is not known how the Il7r gene is transcriptionally regulated during B cell development. The goal of this study is to elucidate the function of the Il7r promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 41 publications
2
35
0
1
Order By: Relevance
“…Gene-targeting studies of the DNA binding GABP␣ subunit have revealed its critical roles during embryogenesis (25), during the reentry of the cell cycle (41), and in synaptic function at the neuromuscular junction (22,24). In the immune system, we and others showed that GABP critically regulates IL-7R␣ expression (5,38). Recently, we demonstrated that GABP is a key component of gene the regulatory network, programming B-lineage commitment and differentiation by directly regulating Pax5 gene expression (39).…”
Section: Vol 28 2008 Gabp␤1l Is Dispensable For Lymphocyte Developmmentioning
confidence: 99%
“…Gene-targeting studies of the DNA binding GABP␣ subunit have revealed its critical roles during embryogenesis (25), during the reentry of the cell cycle (41), and in synaptic function at the neuromuscular junction (22,24). In the immune system, we and others showed that GABP critically regulates IL-7R␣ expression (5,38). Recently, we demonstrated that GABP is a key component of gene the regulatory network, programming B-lineage commitment and differentiation by directly regulating Pax5 gene expression (39).…”
Section: Vol 28 2008 Gabp␤1l Is Dispensable For Lymphocyte Developmmentioning
confidence: 99%
“…GABP␣ is part of a heterodimeric complex that includes GABP␤ (also known as NRF1) that can activate transcription and recruit histone acetyltransferases (30). In B cell progenitors, both GABP and PU.1 drive IL-7R␣ expression (28,31), but in thymocytes and naive T cells GABP alone performs this function (29). The reason behind the separation of functions of PU.1 and GABP in the different lymphocyte lineages is not clear.…”
mentioning
confidence: 99%
“…In addition, a few transcription factors have been identified that directly bind to and control Il7ra expression. Two transcription factors of the Ets family, PU.1 and GA binding protein ␣ (GABP␣; also known as NRF-2 and E4TF1-60), bind to the same site in the Il7ra promoter and activate its transcription (27)(28)(29). GABP␣ is part of a heterodimeric complex that includes GABP␤ (also known as NRF1) that can activate transcription and recruit histone acetyltransferases (30).…”
mentioning
confidence: 99%
“…Several transcription factors that control Il7r gene expression have been identified. The promoter of Il7r contains binding sites for the PU.1 transcription factor, which is necessary for the IL-7R␣ expression in developing B cells (8,9). The same site is occupied in T cells by another ETS family transcription factor, GABP (10).…”
mentioning
confidence: 99%